2001
DOI: 10.1051/lait:2001153
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the texture of Salers cheese by sensory analysis and physical methods

Abstract: -The 25 investigated Salers cheeses graded by the professional committee offered a large range of textures. Their texture characteristics were investigated by sensory analysis, rheological measurements and fluorescence spectroscopy. The 8 sensory attributes generated by the panel included the evaluation of mechanical, geometric and surface properties, and allowed the characterisation of the texture of the investigated cheeses. The stress values at 20% compression ranged between 0.073 and 0.290 kPa. The fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 16 publications
2
20
0
1
Order By: Relevance
“…2b. The spectra were similar to those obtained earlier (Herbert et al 2000;Kulmyrzaev et al 2005a;Lebecque et al 2001;Mazerolles et al 2006). Fluorescence intensities at the characteristic wavelengths and shapes of the excitation spectra of vitamin A considerably changed during ripening of the cheeses (Fig.…”
Section: Spectral Characteristicssupporting
confidence: 85%
“…2b. The spectra were similar to those obtained earlier (Herbert et al 2000;Kulmyrzaev et al 2005a;Lebecque et al 2001;Mazerolles et al 2006). Fluorescence intensities at the characteristic wavelengths and shapes of the excitation spectra of vitamin A considerably changed during ripening of the cheeses (Fig.…”
Section: Spectral Characteristicssupporting
confidence: 85%
“…In addition, it has been reported by Lebecque et al (2001) that high correlations were observed between texture sensory attributes, rheological data, and fluorescence data recorded on Salers cheeses. Considering fluorescence of vitamin A and sensory profiles, the first two pairs of canonical variates have been found to be correlated with squared canonical correlation coefficients equal to 0.85 and 0.69.…”
Section: Ccswa Of Synchronous Fluorescence Mid-infrared and Rheologmentioning
confidence: 80%
“…For the CCA analysis, the rheological parameters and the fluorescence spectra recorded at the same temperatures, i.e., 5,10,15,20,25,30,35,40, 50 and 60 °C were considered. It has been successfully applied to comparing fluorescence and mid-infrared spectra of semi-hard cheeses [12] and rheology data and sensory data of Salers cheese [24]. In both cases, the authors were able to provide relevant similarity maps of the samples that were not immediately found by principal component analysis.…”
Section: Canonical Correlation Analysis Of Fluorescence and Rheologicmentioning
confidence: 99%